Spatiotemporal Evolution of Regional Green Economy under Administrative Division Adjustment on Applications of Artificial Intelligence: A Case Study of the Guangdong-Hong Kong-Macao Greater Bay Area. (4th April 2022) - Wang, Xiaoxiao; Shi, Ruiting; Shi, Qiulu
Abstract : In the context of aggravating environmental problems, the concept of green economy, advocated by policies introduced to solve such problems, is being increasingly recognized and emphasized. In addition, digital technologies, represented by the Internet, big data, and artificial intelligence, are constantly integrating with economic and social fields, gradually becoming an important driving force for economic and social development, and also bringing certain positive environmental effects. This study investigated the spatiotemporal evolution characteristics of the green economy of the Guangdong-Hong Kong-Macao Greater Bay Area (GBA) in the past three decades (1987-2018) under the background of administrative division adjustment and artificial intelligence development. First, the overall green economic development level of the GBA from 1987 to 2018 was analyzed using the superefficiency slack-based measure model. Then, the spatial pattern evolution characteristics and regional differences of green economy in the GBA in this period were assessed by the exploratory spatial data analysis model. According to the results of this study, (1) the green economic development levels of Guangzhou, Shenzhen, Foshan, Zhaoqing, and Hong Kong in the GBA always followed an increasing trend from 1987 to 2018. To be specific, Foshan, Zhongshan, Hong Kong, and Macao ranked among the top areas in the GBA in terms of average green economic development level; moreover, a strong positive correlation was found between economic strength and green economic development. (2) The overall green economic development level of the GBA roughly followed a trend of first decreasing and then increasing, fluctuating around 0.45 on average. (3) Clearly, the green economy of various cities in the GBA showed certain correlations in 1987-2005, but with great fluctuations. However, no spatial correlation was observed after 2006. On the whole, in the GBA, the spatial agglomeration of green economy was weak. (4) There was a general lack of obvious spatial agglomeration in the overall green economic development of the GBA, especially in western Guangdong. In contrast, spatial agglomeration was obvious in eastern Guangdong.